PERM SCHOOL OF SOLVENT EXTRACTION: FORMATION AND DEVELOPMENT - Zabolotnykh, S.A.; Denisova, S.A.; Lesnov, A.E. (Perm Federal Research Centre Journal, 2016)
The paper is devoted to the formation and development of the solvent extraction method in higher educational institutions of Perm. Data on the study of new extraction reagents, their properties and application in practice of analytical chemistry are presented along with the information on the development of new and innovative extraction systems based on the chemical interaction between components or on the salting out-effect of surfactants by inorganic compounds.